GlycA, hsCRP differentially associated with MI, ischemic stroke: In the Dallas Heart Study and Multi-Ethnic Study of Atherosclerosis - Kayla A. Riggs; Parag H. Joshi; Amit Khera; James D. Otvos; Philip Greenland; Colby R. Ayers; Anand Rohatgi (Elsevier, 2022)
Objective: Inflammatory markers are associated with cardiovascular disease (CVD); however, the ability to specifically predict myocardial infarction (MI) as well as ischemic stroke remains unknown. There has not been a direct comparison of the associations between GlycA and hsCRP and MI and ischemic stroke in a multi-ethnic pooled cohort. Methods: Multi-center, multi-ethnic, population-based community prospective pooled cohort of the Dallas Heart Study (DHS) and Multi-Ethnic Study of Atherosclerosis (MESA). 9,785 participants without baseline CVD enrolled with median follow-up of 13.4 years. Fatal/nonfatal MI and fatal/nonfatal ischemic stroke were assessed separately and then combined. Results: GlycA was moderately associated with hsCRP (R=0.58 in DHS and R=0.55 in MESA). In adjusted Cox proportional hazards models with competing risk adjusted for both inflammatory markers, GlycA was directly associated with MI (HR Q4 vs. Q1 1.90, 95% CI 1.39 to 2.58), whereas hsCRP was not (HR Q4 vs. Q1 0.92, 95% CI 0.70 to 1.21). Conversely, hsCRP was directly associated with ischemic stroke (HR Q4 vs. Q1 1.73, 95% CI 1.15 to 2.59), but GlycA was not (HR Q4 vs. Q1 1.21, 95% CI 0.77 to 1.90). GlycA improved net reclassification for MI and hsCRP did so for ischemic stroke. Conclusions: Although both GlycA and hsCRP were associated with incident CVD, GlycA more strongly predicted incident MI, and hsCRP more strongly predicted ischemic stroke.